2016
DOI: 10.1002/2016jc011861
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of mesoscale activity on the water masses and circulation in the Coral Sea

Abstract: The climatological vision of the circulation within the Coral Sea is today well established with the westward circulation of two main jets, the North Caledonian Jet (NCJ) and the North Vanuatu Jet (NVJ) as a consequence of the separation of the South Equatorial Current (SEC) on the islands of New Caledonia, Vanuatu, and Fiji. Each jet has its own dynamic and transports different water masses across the Coral Sea. The influence of mesoscale activity on mean flow and on water mass exchanges is not yet fully expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 48 publications
3
19
0
Order By: Relevance
“…4 top) and the fate (Fig.4 bottom) that eddy-eddy interactions might be responsible for the emergence of complex paths between the NVJ and the NCJ. Indeed it matches the area described by Rousselet et al (2016) as the region of exchange between NCJ and NVJ waters through eddy trapping and transport. We identify a probable water mass mixing area, in the Coral Sea center, through complex mesoscale stirring.…”
Section: Mesoscale Activity and Trajectories Of Surface Watersmentioning
confidence: 63%
“…4 top) and the fate (Fig.4 bottom) that eddy-eddy interactions might be responsible for the emergence of complex paths between the NVJ and the NCJ. Indeed it matches the area described by Rousselet et al (2016) as the region of exchange between NCJ and NVJ waters through eddy trapping and transport. We identify a probable water mass mixing area, in the Coral Sea center, through complex mesoscale stirring.…”
Section: Mesoscale Activity and Trajectories Of Surface Watersmentioning
confidence: 63%
“…They tend to have higher amplitudes than in the same latitude range east of Vanuatu, and have a signature in temperature and salinity higher than 0.3°C and 0.02, respectively, down to ∼500 m depth. Rousselet et al () suggested that AE participate in the transport and mixing of water masses from the NVJ to the NCJ in this Coral Sea Countercurrent region. In agreement with this study, we find that AE in the Coral Sea countercurrent region are indeed able to trap waters above 200 m, to transport salty SPTW waters from the NVJ to the NCJ above σ = 25 kg m −3 , and to contribute to the mixing of these two water masses.…”
Section: Discussionmentioning
confidence: 99%
“…Such a positive anomaly cannot result from diapycnal mixing with the over and underlying fresher water masses; it thus implies a trapping and an advection of saltier waters from the east and north (see trajectories in Figure ). This confirms previous assertions that AE in the Coral Sea Countercurrent region may contribute to the mixing of water masses from the saltier NVJ waters to the fresher NCJ waters (Rousselet et al, ). The trapping is however mainly restricted to the upper thermocline waters, and does not seem to affect the lower thermocline nor intermediate waters.…”
Section: Eddy Vertical Structurementioning
confidence: 96%
See 2 more Smart Citations